How We Did It: A User Experience Seating Survey Success Story. Issue 4 (1st October 2016) - Brown, Molly
ABSTRACT: Academic libraries are changing – the emphasis is no longer focusing solely on collecting print material, because the way we find information has changed radically in the last two decades. As a User Experience (UX) Librarian, my focus is to assess and improve the services that our patrons come in contact with. The State University of New York at Oneonta's Milne Library will undergo a renovation in 2017 and prior to the architectural plans being completed, we wondered what will the alterations would mean for our users? Our UX group took the initiative to study the spaces and seating choices students use when in the library, to determine what would be most beneficial for them in the renovated building. During the fall semester of 2015, coinciding with the weeks when the library was most active, our group undertook a two week study of the seating choices the students had at their disposal in the hopes that we could understand what motivated them to work in certain areas, as well as improve what we offer them in a renovated building. The study required a great amount of time and dedication from library faculty, staff and student workers, but in the end we gathered an enormous amount of data that directed our decisions toward the final renovation in ways that we hope will make the library a more welcoming and engaging place for all our patrons.